Kekerasan Seksual dalam Rumah Tangga Perspektif Tafsir Al-Qurthubi (Kajian Q.S An-Nisa Ayat 19) - Nila Qonita Auliya; Yeti Dahliana (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2023)
Sexual violence within households is often a common occurrence in society. The Complaints Report by the National Commission on Violence Against Women throughout the year 2022 noted that sexual violence is the predominant form of violence with 2,228 cases (38.21%), followed by psychological violence with 2,083 cases (35.72%). This number increased by 15.2% from the previous year, totaling 21,753 cases. When looking at this data, the issue of violence against women cannot be underestimated.This research aims to explore Qurthubi's understanding in his Tafsir Al-Qurthubi regarding verse 19 of Surah An-Nisa. The analysis results will provide perspectives from the Quran and solutions to address the issue of sexual violence within households. In this study, the method employed is qualitative. The primary data source is Imam Qurthubi's Tafsir Al-Qurthubi, and additional data sources include relevant books for the research. To access this data, the author conducted library research by analyzing, clarifying, and presenting the necessary information.The findings of this research indicate that in Qurthubi's tafsir, the discussed form of sexual violence involves acts of violence that occur when one party forces or coerces themselves upon another. This tafsir also emphasizes the importance of gentle and wise communication in resolving conflicts within the household and warns about the consequences of unfair behavior towards one's wife.